Kontribusi layanan informasi terhadap perencanaan karier siswa - Ananda de Viska; Cindy Marisa; T. Sunarto (Universitas Indraprasta PGRI, 2022)
career is one of the fields in counseling and information service is a service that can assist students in making career plans. The purpose of this study, among others, is to determine whether there is a significant influence between information services and career planning. In this study, researchers used quantitative methods by using instruments in the form of questionnaires or questionnaires in data collection. The target population is all students, the sample is from class XII at SMK Tirtajaya, totaling 89 students. Based on research data that has been done by field researchers to determine the effect of information services on student career planning. Then it can be concluded that there is a significant influence between the information services and career planning of students at SMK Tirtajaya Depok.